1989
DOI: 10.1042/bj2570665
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in the expression of mitochondrial protein mRNA during the development of brown adipose tissue in bovine and ovine species. Sudden occurrence of uncoupling protein mRNA during embryogenesis and its disappearance after birth

Abstract: Samples of adipose tissue were obtained from different sites in bovine and ovine foetuses and newborns. RNA was isolated and analysed using bovine cDNA and ovine genomic probe for uncoupling protein (UCP), cDNA for subunits III and IV of cytochrome c oxidase and cDNA for ADP/ATP carrier. UCP mRNA was characterized for the first time in foetal bovine and ovine adipose tissue. It appeared later than mRNA of cytochrome c oxidase subunit III, and increased dramatically at birth (10-fold). ADP/ATP carrier mRNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 36 publications
9
72
1
3
Order By: Relevance
“…In the last 20 days before birth most of the AT is abdominal and intermuscular, with little subcutaneous AT (Robelin et al, 1985). In cattle and sheep at birth, the different AT depots, except for the subcutaneous depot in some bovine breeds , can be considered as brown due to the high expression of UCP1, cytochrome c oxidase and ADP/ATP carrier protein (Casteilla et al, 1987;Casteilla et al, 1989). UCP1 mRNA reaches its highest level in the various BAT at birth and is no longer detectable 2 days later in cattle (Casteilla et al, 1987), and sheep, probably as the result of a sharp decline in the expression of peroxisome proliferatoractivated receptor-a (PPARa) and peroxisome proliferatoractivated receptor-c coactivator-1a (PGC-1a) (Lomax et al, 2007).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 days before birth most of the AT is abdominal and intermuscular, with little subcutaneous AT (Robelin et al, 1985). In cattle and sheep at birth, the different AT depots, except for the subcutaneous depot in some bovine breeds , can be considered as brown due to the high expression of UCP1, cytochrome c oxidase and ADP/ATP carrier protein (Casteilla et al, 1987;Casteilla et al, 1989). UCP1 mRNA reaches its highest level in the various BAT at birth and is no longer detectable 2 days later in cattle (Casteilla et al, 1987), and sheep, probably as the result of a sharp decline in the expression of peroxisome proliferatoractivated receptor-a (PPARa) and peroxisome proliferatoractivated receptor-c coactivator-1a (PGC-1a) (Lomax et al, 2007).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
“…To date, only HSL has been identified in bovine WAT through its mRNA abundance (Bonnet et al, 1998;Sumner and Mcnamara, 2007;Xu et al, 2008) and its activity (Sprinkle et al, 1998;Kazala et al, 2003). The thermogenic protein UCP1, together with enzymes involved in the citric acid cycle and the respiratory chain, are expressed in bovine foetal BAT, allowing FA oxidation and heat production (Casteilla et al, 1989;Smith et al, 2004;Hocquette et al, 2006).…”
Section: Dynamics Of At Growthmentioning
confidence: 99%
“…UCP is present before birth in lambs and calves but exhibits a low thermogenic activity (Casteilla, Forest, Robelin, Ricquier, Lombert & Ailand, 1987;Clarke, Bryant, Lomax & Symonds, 1997a). At birth, the newborn is subjected to a dramatic decline in environmental temperature, and this cold exposure appears to be the signal for a rapid rise in metabolic rate in conjunction with an increase in both the amount of UCP and its thermogenic activity (Clarke, Heasman, Firth & Symonds, 1997b), as well as the level of mRNA for UCP (Casteilla, Champigny, Bouilland, Robelin & Ricquier, 1989). The ability to maximize BAT function after birth is important clinically, since this can be compromised by Caesarean section birth (Christensson et al 1993;Clarke et al 1997b), and also agriculturally, since a high proportion of the 1-4 million annual lamb deaths in the British sheep industry are due to hypothermia (Slee, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In perirenal adipose tissue, which is the major adipose store in newborn lambs and goats, UCP mRNA disappears rapidly after birth and is closely followed by the loss of UCP (Casteilla et al 1987(Casteilla et al , 1989Trayhurn, Thomas & Keith, 1993). It is known that the rate of loss of UCP can be delayed by hand-rearing at a cool ambient temperature (Darby, Clarke, Lomax & Symonds, 1996), but the exact time course of postnatal changes in adipose tissue development or the extent to which they may be linked to changes in body temperature remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…The few published metabolic features of foetal bovine AT have been obtained on perirenal AT. It has been shown that in the last third of foetal growth or at birth, bovine perirenal AT exhibits in vitro lipogenesis from acetate and palmitate (Landis et al, 2002), expresses lipoprotein lipase (LPL; Hocquette et al, 2006) and uncoupling protein 1 (UCP 1; Casteilla et al, 1989), and contains multilocular adipocytes with a high number of mitochondria that highlight the presence of brown adipocytes in foetal AT (Alexander et al, 1975;Landis et al, 2002). However, we recently reported that at the end of foetal life (260 dpc), bovine perirenal and intermuscular AT are a mixture of brown and mainly white adipocytes (Taga et al, 2011).…”
Section: Introductionmentioning
confidence: 99%